Diálogos entre dois contos machadianos : leituras de “O segredo de Augusta” e “Uma senhora” - Camargo, Eduarda Rita Nicoletti (Universidade Federal de São Carlos, 2017)
This work aims to study two short stories by the writer Machado de Assis, taking in consideration their thematic approximation, leading one to believe that the second short story, "Uma senhora", from 1883, would be the rewrite of a previous short story, "O segredo de Augusta”, from 1868. In order to achieve this, the analysis take into consideration the leitmotiv of the vain woman and the figure of the narrator and in what way the narrator articulates the characters throughout the narrative. Thus, the author uses the theme of a previous short story, still marked by romantic characteristics and rewrite it, guaranteeing a formal improvement in the process of rewriting.
Keywords: Conto; Reescrita; Short story; Rewriting; LINGUISTICA, LETRAS E ARTES::LETRAS